Lithium-ion battery
The lithium ion battery design addresses the incompatibility between specific capacity and safety by using a composite of lithium manganese iron phosphate and ternary materials with silicon oxide and a lithium supplementary layer, achieving enhanced performance and safety through optimized electrode materials and structures.
Patent Information
- Application Number
- JP2023528220
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-11
- Filing Date
- 2021-11-10
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2041-11-10
AI Technical Summary
Conventional lithium iron phosphate-ternary lithium ion batteries face issues of incompatibility between specific capacity and safety due to mismatched charge and discharge voltage plateaus, leading to low performance and safety concerns.
A lithium ion battery design incorporating a positive electrode active material composed of lithium manganese iron phosphate and a ternary material, with a negative electrode active material comprising a carbon material and silicon oxide, and a lithium supplementary layer to ensure adequate active lithium content, along with controlled density and thickness of electrode plates and separators, enhances compatibility and safety.
The battery achieves improved charge and discharge capacity, extended cycle life, and enhanced safety with a specific capacity of 250 Wh/kg and a capacity retention rate of 76% after 2000 cycles, while maintaining safety below 255°C, outperforming conventional designs.
Smart Images

Figure 0007660197000002 
Figure 0007660197000001
Abstract
Description
[Technical field]
[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims priority to Chinese Patent Application No. 202011253796.3, entitled "Lithium Ion Battery," filed with the State Intellectual Property Office of the People's Republic of China on November 11, 2020, the entire contents of which are incorporated herein by reference.
[0002] This application relates to the field of power equipment, and in particular to lithium ion batteries. [Background technology]
[0003] With the gradual increase in awareness of energy and environmental protection, new energy vehicles have made remarkable development in recent years. Electric vehicles have become one of the main trends. In the power batteries of electric vehicles, lithium ion batteries occupy a very important position, and lithium iron phosphate and NCM (nickel cobalt manganese) ternary materials have become the main choice of positive electrode active materials for lithium ion batteries.
[0004] However, the lithium iron phosphate-ternary lithium ion power battery in the prior art has certain defects. For example, the voltage plateau of lithium iron phosphate is about 3.18V, while the voltage plateau of NCM ternary material is about 3.65V. When lithium iron phosphate and NCM ternary material are mixed, there is a problem that the charge and discharge voltage plateaus are not compatible, resulting in low specific capacity and low safety of the lithium ion battery. Summary of the Invention [Problem to be solved by the invention]
[0005] The embodiments of the present application provide a lithium-ion battery that solves the problem of the incompatibility between specific capacity and safety of conventional lithium-ion batteries. [Means for solving the problem]
[0006] In order to solve the above problems, the embodiment of the present application uses the following technical means. The lithium ion battery according to the embodiment of the present application: The battery includes a positive electrode plate, a separator, and a negative electrode plate, the separator being provided between the positive electrode plate and the negative electrode plate; The positive electrode plate includes a positive electrode current collector and a positive electrode active layer which are laminated in this order, the positive electrode active material in the positive electrode active layer includes lithium manganese iron phosphate and a ternary material, and based on the total mass of the positive electrode active material, the mass percentage of the lithium manganese iron phosphate is in the range of 70% to 90%, and the mass percentage of the ternary material is in the range of 10% to 30%, The negative electrode plate includes a negative electrode current collector and a negative electrode active layer, which are laminated in order. The negative electrode active layer includes a composite layer and a lithium supplementary layer. The negative electrode active material in the composite layer is a carbon material and SiO x The mass percentage of the carbon material is in the range of 70% to 90% based on the total mass of the negative electrode active material, and the SiO x The mass percentage range of is 10% to 30%, and the surface density of lithium in the lithium replenishment layer is m2 = a × M1 × m1 × δ × (1-η) / M2, In the formula, m2 is in g / dm 2 and M1 is SiO x The unit of the discharge specific capacity is mAh / g, m1 is the surface density of the negative electrode plate on both sides, and m1 is the unit of g / dm 2 and δ is the SiO x is the mass percentage of the material, and η is SiO x where the initial efficiency is the ratio of the initial discharge capacity to the initial charge capacity, M2 is the value of the specific capacity of lithium, the unit of the specific capacity is mAh / g, the value of a is in the range of 1.05 to 1.15, and the value of x is in the range of 0.6 to 1.5.
[0007] In some embodiments of the present application, based on the total mass of the positive electrode active material, the mass percentage range of the lithium manganese iron phosphate is 78% to 83%, and the mass percentage range of the ternary material is 17% to 22%, The mass percentage of the carbon material is in the range of 83% to 88% based on the total mass of the negative electrode active material, and the SiO x The mass percentage range is 12% to 17%.
[0008] In some embodiments of the present application, the range of the two-sided areal density of the positive plate is 4.5 g / dm 2 ~5.0g / dm 2 and the range of the compaction density of the positive electrode plate is 2.7 g / cm 3 ~2.8g / cm 3 and the range of the surface density of the negative electrode plate on both sides is 1.56 g / dm 2 ~1.92g / dm 2 and the range of the compaction density of the negative electrode plate is 1.60 g / cm 3 ~1.65g / cm 3 It is.
[0009] In some embodiments of the present application, the general formula of the ternary material is LiNi a1 Co b1 X c1 O2, In the formula, 0≦a1≦1, 0≦b1≦1, 0≦c1≦1, and a1+b1+c1=1; and X is at least one metal element of subgroup III to main group V.
[0010] In some embodiments of the present application, the carbon material includes at least one of hard carbon and secondary carbon-coated graphite.
[0011] In some embodiments of the present application, the value of x ranges from 0.8 to 1.2.
[0012] In some embodiments of the present application, the electrolyte injection coefficient in the lithium ion battery is within 2.9 to 3.2.
[0013] In some embodiments of the present application, the separator is provided between the positive electrode plate and the negative electrode plate, and the separator includes a polymer layer, a ceramic layer, and an adhesive layer laminated in that order, the polymer layer having a thickness ranging from 5.5 μm to 9 μm, the ceramic layer having a thickness ranging from 1.0 μm to 3.0 μm, and the adhesive layer having a thickness ranging from 1.0 μm to 3.0 μm.
[0014] In some embodiments of the present application, the thickness of the positive electrode current collector is in the range of 7 μm to 13.5 μm, and the thickness of the negative electrode current collector is in the range of 3.5 μm to 7 μm. Effect of the Invention
[0015] The technical means used in the embodiments of the present application can achieve the following beneficial effects:
[0016] The lithium ion battery according to the embodiment of the present application includes a positive electrode plate, a separator, and a negative electrode plate, the separator being disposed between the positive electrode plate and the negative electrode plate, the positive electrode plate including a positive electrode current collector and a positive electrode active layer which are laminated in order, the positive electrode active material in the positive electrode active layer including lithium manganese iron phosphate and a ternary material, the negative electrode plate including a negative electrode current collector and a negative electrode active layer which are laminated in order, the negative electrode active layer including a composite layer and a lithium supplement layer, the negative electrode active material in the composite layer including a carbon material and SiO x The lithium surface density m2 in the lithium supplement layer is a×M1×m1×δ×(1−η) / M2. The positive electrode active material of the lithium ion battery according to the embodiment of the present application is a composite material of lithium manganese iron phosphate and a ternary material, and the negative electrode active material is a composite material of a carbon material and SiO x Using a composite material with SiO x In addition to improving the charge and discharge capacity of the negative electrode active layer, the lithium supplementary layer is provided to ensure the content of active lithium in the negative electrode active layer, and the multiple characteristic requirements of the specific capacity, service life and safety of the lithium ion battery are met.
[0017] Additional aspects and advantages of the disclosure will be set forth in part in the description that follows, and in part will be obvious from the description, or may be learned by practice of the disclosure. [Brief description of the drawings]
[0018] The drawings described herein are intended to facilitate understanding of the present application and constitute a part of the present application, and the illustrative embodiments and their description are intended to explain the present application and are not intended to limit the present application.
[0019] [Figure 1] FIG. 1 is a schematic diagram of a lithium ion battery according to an embodiment of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] In order to make the objectives, technical means and advantages of the present invention clearer, the technical means of the present application will be described clearly and completely below with reference to specific embodiments of the present application and corresponding drawings. Obviously, the described embodiments are only some of the embodiments of the present application, and are not all of the embodiments. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without making creative efforts are all within the scope of protection of the present application.
[0021] The terms "first", "second", etc. in the specification and claims of this application are used to distinguish between similar objects and do not describe a particular order or priority. It should be understood that the data used in this manner may be interchanged as appropriate so that the embodiments of this application can be practiced, for example, in an order other than that shown or described herein, and that the objects distinguished by "first", "second", etc. are generally of the same type and do not limit the number of objects, for example, the first object may be one or more. Also, "and / or" in the specification and claims represents at least one of the connected objects, and the symbol " / " generally represents that the related objects before and after are in an "or" relationship.
[0022] Hereinafter, technical means according to each embodiment of the present application will be described in detail with reference to the drawings.
[0023] As shown in FIG. 1, the lithium ion battery according to the embodiment of the present application has: The battery includes a positive electrode plate 1, a separator 3, and a negative electrode plate 2, and the separator 3 is provided between the positive electrode plate 1 and the negative electrode plate 2. The positive electrode plate 1 includes a positive electrode current collector 12 and a positive electrode active layer 11 which are laminated in this order. The positive electrode active material in the positive electrode active layer 11 includes LMFP (lithium manganese iron phosphate) and a ternary material. The negative electrode plate 2 includes a negative electrode current collector 22 and a negative electrode active layer 21 which are laminated in this order. The negative electrode active layer 21 includes a composite layer 211 and a lithium supplementary layer 212. The composite layer 211 is provided on the negative electrode current collector 22. The lithium supplementary layer 212 is provided on the side of the composite layer 211 away from the negative electrode current collector 22. The negative electrode active material in the composite layer 211 includes a carbon material and SiO x (silicon oxide), where the silicon oxide includes, but is not limited to, silicon monoxide, and may also include silicon oxide having less than one oxygen atom coordinated to a silicon atom, and silicon oxide having more than one oxygen atom coordinated to a silicon atom.
[0024] Based on the total mass of the positive electrode active material, the mass percentage of the LMFP is in the range of 70% to 90%, the mass percentage of the ternary material is in the range of 10% to 30%, and based on the total mass of the negative electrode active material, the mass percentage of the carbon material is in the range of 70% to 90%, and SiO x The mass percentage range of is 10% to 30%, the lithium supplement material of the lithium supplement layer 212 may be lithium powder or lithium foil, and the surface density of lithium in the lithium supplement layer 212 is m2=a×M1×m1×δ×(1−η) / M2, In the formula, m2 is in g / dm 2 and M1 is SiO x The unit of the discharge specific capacity is mAh / g, m1 is the surface density of the negative electrode plate on both sides, and the unit of m1 is g / dm 2 and δ is the SiO x The mass percentage of the material, that is, SiO in the negative electrode active material xThe mass percentage δ ranges from 10% to 30%, and η is SiO x where the initial efficiency is the ratio of the initial discharge capacity to the initial charge capacity, M2 is the value of the specific capacity of lithium, the unit of the specific capacity is mAh / g, the value of a is in the range of 1.05 to 1.15, and the value of x is in the range of 0.6 to 1.5.
[0025] Specifically, when the value of x is in the range of 0.6 to 1.5, SiO x The material has the characteristics of high charge / discharge capacity and small volume expansion. SiO x In the formula, when x is smaller than 0.6, SiO x The characteristics of the SEI film are close to those of pure silicon. In other words, if the volume expansion during the charge / discharge process is large, the SEI film will be continuously destroyed and repaired, consuming the active lithium in the positive electrode material and deteriorating the cycle characteristics. In addition, repeated expansion will cause the SiO x This causes cracking and differentiation of the material, reducing the stability of the structure and affecting the performance of lithium-ion batteries. x In the formula, when x is greater than 1.5, SiO x The proportion of lithium reacting with SiO to produce lithium silicate, which is not electrochemically active, increases. x This reduces the specific capacity of the negative electrode and also reduces the cycle characteristics of the lithium-ion battery.
[0026] Specifically, the negative electrode active material of the lithium ion battery forms an SEI film during the charge and discharge process, and the formation of the SEI film requires the consumption of some of the reversible active lithium in the positive electrode active material, and the initial efficiency of the LMFP is higher than that of the graphite, and the LMFP material loses irreversible lithium due to the initial efficiency, which is not sufficient for the consumption by graphite and the formation of the SEI film, so that in the process of forming the SEI film on the negative electrode active material, other active lithium ions of the LMFP need to be further consumed, causing the loss of active lithium ions of the LMFP, which reduces the actual specific capacity of the LMFP itself in the whole battery, and reduces the energy density of the lithium ion battery. Ternary materials have the problem of low initial efficiency, and most of the irreversible lithium remaining in the negative electrode can be used to form the SEI film of the negative electrode active material in the negative electrode plate 2, thereby avoiding the consumption of active lithium ions of the LMFP in the process of forming the SEI film on the negative electrode active material, which is essentially equivalent to replenishing lithium to the LMFP, and improving the performance of the specific capacity of the LMFP. In addition, the compaction density of LMFP is low, and the addition of a ternary material having a high compaction density can improve the compaction density of the positive electrode plate 1, and further improve the energy density of the lithium ion battery. Therefore, the positive electrode active material of the lithium ion battery of the present application can fully exhibit the specific capacity and safety of LMFP, and can improve the capacity, service life, and safety of the lithium ion battery.
[0027] The negative electrode active material according to the embodiment of the present application contains silicon oxide. The discharge specific capacity M1 of silicon oxide can reach 1300mAh / g to 1500mAh / g, which is 3 to 5 times the discharge specific capacity of conventional carbon materials. The initial efficiency η of silicon oxide can reach 82% to 88%, so that the addition of silicon oxide can significantly improve the charge and discharge capacity of the negative electrode active material. Covering The amount of material and the thickness of the negative electrode active layer and the negative electrode plate can be reduced. However, silicon oxide displaces many irreversible lithium ions during the initial charge and discharge process. consumptionIn the lithium ion battery according to the embodiment of the present application, the negative electrode plate 2 is supplemented with lithium, that is, the negative electrode active layer 21 includes a composite layer 211 and a lithium supplemented layer 212, which ensures the active lithium capacity of the positive electrode active material during charging and discharging, and improves the cycle life of the lithium ion battery.
[0028] The positive active material of the lithium ion battery according to the embodiment of the present application uses a composite material of LMFP and a ternary material, the negative active layer 21 uses a composite design of the negative active material of the composite layer 211 and the lithium supplementary layer 212, and the silicon oxide improves the charge and discharge capacity of the negative active layer 21, while the addition of the lithium supplementary layer 212 ensures the content of reversible active lithium in the battery. The energy density of the lithium ion battery according to the embodiment of the present application can reach 250Wh / kg, the capacity retention rate after 2000 charge and discharge cycles can reach 76% or more, and the DSC trigger temperature of the positive active material is higher than 255°C, that is, it can operate safely within the range of 255°C or less, and the specific capacity, service life and safety of the lithium ion battery are improved.
[0029] According to one embodiment of the present application, based on the total mass of the positive electrode active material, the mass percentage of the LMFP is in the range of 78% to 83%, and the mass percentage of the ternary material is in the range of 17% to 22%. 2 ~5.0g / dm 2 and the range of the compaction density of the positive electrode plate 1 is 2.7 g / cm 3 ~2.8g / cm 3 Specifically, the above-mentioned double-sided surface density is the mass of the electrode material applied to a unit area of the foil material when the foil material is coated on both sides.
[0030] Specifically, when a ternary material and an LMFP material are mixed in the positive electrode active material of a conventional lithium-ion battery, if the ratio of the ternary material in the positive electrode active material is too low, the ternary material has low initial efficiency, and the lost lithium ions are not sufficient for consumption by graphite and formation of an SEI film, so that the LMFP needs to consume extra lithium ions so that an SEI film is formed on the graphite in the negative electrode plate, and thus the actual specific capacity of the LMFP in the positive electrode plate is low. On the other hand, if the ratio of the ternary material in the positive electrode active material is too high, on the one hand, the structural stability of the ternary material is low compared to that of the LMFP, so that the cycle capacity retention rate of the mixed system of the positive electrode active material is low, and on the other hand, the safety of the ternary material during the charge and discharge process is low, which is disadvantageous to the safe use of the lithium-ion battery. Therefore, when the initial efficiency of the positive electrode active material mixed in the lithium ion battery according to the embodiment of the present application is balanced with the initial efficiency of the negative electrode active material, that is, the sum of the irreversible active lithium of the ternary material and the LMFP material can just meet the formation of the SEI film in the negative electrode active material, and ensure the capacity of the LMFP material in the positive electrode active material. In addition, the control of the surface density and compaction density of both sides of the positive electrode plate 1 can effectively adjust the thickness of the positive electrode active material, that is, the surface density of both sides of the positive electrode plate 1 divided by its compaction density is the thickness of the positive electrode active material. By adjusting the thickness of the positive electrode active material, the total capacity of the positive electrode active material can be effectively controlled and the energy density of the battery can be improved.
[0031] According to one embodiment of the present application, the general formula of the ternary material is LiNi a1 Co b1 X c1 O2, In the formula, 0≦a1≦1, 0≦b1≦1, 0≦c1≦1, and a1+b1+c1=1; X is at least one metal element from subgroup III to main group V; and X may be one or more of Mn, Al, Zr, Ti, Y, Sr, and W; and the mass fraction of Ni in the ternary material is in the range of 80% to 95%.
[0032] Specifically, the Mn element in the ternary material is partially or entirely replaced with elements such as Al, Zr, Ti, Y, Sr and W, so as to improve the safety stability and perfection of the crystal structure of the ternary material. In addition, when the mass fraction of Ni in the ternary material is in the range of 80%-95%, the ternary material is called a high-nickel ternary material, which has the advantages of low cost, high energy density, high reversible capacity, environmental friendliness, etc., and can greatly improve the specific capacity and cycle life of lithium-ion batteries. Although the safety of the high-nickel ternary material is low, when the mixing ratio of LMFP and high-nickel ternary material is within a certain range, the safety of the system can be further closer to the safety of the LMFP system, and the safety of use of the user can be guaranteed.
[0033] In one embodiment of the present application, the mass percentage of the carbon material is in the range of 83% to 88% based on the total mass of the negative electrode active material, and SiO x The mass percentage range is 12% to 17%. The surface density range of the negative electrode plate 2 on both sides is 1.56 g / dm 2 ~1.92g / dm 2 That is, the range of the surface density m1 of the negative electrode plate 2 is 1.56 g / dm 2 ~1.92g / dm 2 The range of the compaction density of the negative electrode plate 2 is 1.60 g / cm 3 ~1.65g / cm 3 The electrolyte injection coefficient of the lithium ion battery is within a range of 2.9 to 3.2.
[0034] Specifically, the carbon material in the negative electrode active material can ensure the reversible capacity of the lithium ion battery, and the silicon oxide can improve the charge and discharge capacity of the negative electrode active material. If the carbon material content in the negative electrode active material is too high, it is disadvantageous to improve the capacity of the negative electrode active material, and the addition of excessive silicon oxide generates a large volume expansion, which is disadvantageous to the structural stability of the negative electrode material and the battery cycle characteristics. Therefore, in the lithium ion battery according to the embodiment of the present application, the mass percentage of the carbon material in the negative electrode active material is controlled within the range of 83% to 88%, that is, the mass percentage of silicon oxide is in the range of 12% to 17%. The relative stability of the structure of the lithium ion battery is ensured, and at the same time, the specific capacity of the lithium ion battery is improved. In addition, the control of the both-side areal density and compaction density of the negative electrode plate 2 can effectively adjust the thickness of the negative electrode active material, that is, the thickness of the negative electrode active material is obtained by dividing the both-side areal density of the negative electrode plate 2 by its compaction density. By adjusting the thickness of the negative electrode active material, the capacity density and rate characteristics of the negative electrode active layer 21 can be ensured.
[0035] In one embodiment of the present application, the carbon material includes at least one of hard carbon and secondary carbon-coated graphite.
[0036] Specifically, hard carbon has the characteristic that the spacing between the sheet layers is wide, so that the volume change of hard carbon is small during the process of desorption of lithium ions during charging and discharging, and when mixed with silicon oxide, the expansion of the negative electrode plate can be alleviated to a certain extent. In addition, the charge and discharge plateaus of hard carbon and silicon oxide are close to each other, so that they can operate simultaneously during the charge and discharge process, which helps to realize high-speed charging of lithium-ion batteries. Secondary particle carbon-coated graphite refers to the secondary granulation of graphite material and the carbon coating treatment on the graphite surface at the same time. Such graphite has the advantages of few side reactions and high charge and discharge efficiency, and more importantly, the volume expansion of the graphite is small during the charge and discharge process.
[0037] In one embodiment of the present application, the value of x in the silicon oxide may be in the range of 0.8 to 1.2. In one specific embodiment of the present application, the value of x in the silicon oxide is in the range of 0.9 to 1.1. The silicon oxide has the characteristics of a higher reversible charge / discharge capacity and a smaller volume expansion than pure silicon and general silicon-based materials such as SiO2.
[0038] In one embodiment of the present application, the separator 3 includes a polymer layer, a ceramic layer, and an adhesive layer. The polymer layer may be PP or PE, which has high chemical stability and can ensure the safety of the lithium-ion battery. The thickness of the polymer layer is in the range of 5.5 μm to 9 μm, the thickness of the ceramic layer is in the range of 1.0 μm to 3.0 μm, and the thickness of the adhesive layer is in the range of 1.0 μm to 3.0 μm.
[0039] Specifically, the stacking order of the separator 3 is a polymer layer, a ceramic layer, and an adhesive layer, that is, the polymer layer is a base layer, and the ceramic layer and the adhesive layer are sequentially provided on the surface thereof, the ceramic layer and the adhesive layer are provided on the side of the polymer layer close to the positive electrode plate 1, the provision of the ceramic layer can improve the oxidation resistance of the separator, and the adhesive layer can improve the connection strength between the separator 3 and the positive electrode plate 1 and prevent misalignment during the assembly and use of the battery. In a specific embodiment, the thickness of the polymer layer is 7 μm, the thickness of the ceramic layer is 2 μm, and the thickness of the adhesive layer is 2 μm.
[0040] According to an embodiment of the present application, as shown in FIG. 1, the thickness of the positive electrode current collector 12 is in the range of 7 μm to 13.5 μm, the thickness of the negative electrode current collector 22 is in the range of 3.5 μm to 7 μm, Positive electrode current collector 12By comprehensively controlling the thickness of the positive electrode current collector 12 and the thickness of the negative electrode current collector 22, the energy density of the lithium ion battery can be effectively exhibited while ensuring the safety of the lithium ion battery. In a specific embodiment, the positive electrode current collector 12 is an aluminum foil with a thickness of 12 μm, and the negative electrode current collector 22 is a copper foil with a thickness of 6 μm.
[0041] In one embodiment of the present application, in order to ensure the structure and the integrity of the conductive network of the positive electrode plate 1, the positive electrode plate 1 may include an adhesive and a conductive agent, and based on the positive electrode active material, the mass parts of the adhesive range from 0.3 to 2.0 parts, and the mass parts of the conductive agent range from 0.5 to 2.5 parts, and in one specific embodiment of the present application, the mass fraction of the conductive agent is 1.0 to 1.8 parts. The conductive agent of the positive electrode plate 1 can use a conductive system in which points and points, points and lines, and points and surfaces are combined, for example, a combination of conductive carbon black, carbon nanotubes, and graphene with different tube diameters is used, and the conductive carbon black can be a dot-like conductive material, the carbon nanotubes can be a line-like conductive material, and the graphene can be a plane-like conductive material, thereby achieving a conductive system in which points, lines, and surfaces are combined. In addition, in order to ensure the structure and the integrity of the conductive network of the negative electrode plate 2, the negative electrode plate 2 may include an adhesive and a conductive agent, and based on the negative electrode active material, the range of the mass parts of the adhesive is 2.5 to 7.5 parts, and the adhesive can be selected from SBR and / or CMC, where SBR is styrene butadiene rubber and CMC is sodium carboxymethyl cellulose, both of which are used as adhesives and thickeners for the negative electrode active layer, and are useful for improving the peel strength of the negative electrode active layer and maintaining a certain flexibility of the negative electrode plate. Based on the negative electrode active material, the range of the mass parts of the conductive agent in the negative electrode plate is 0.2 to 1.5 parts, and in one specific embodiment of the present application, the mass fraction of the conductive agent is 0.5 to 1.2 parts. The conductive agent of the negative electrode plate 2 can also be selected from a conductive system in which points and lines and lines are connected.
[0042] The technical means of the present application will be described in detail below in the form of specific examples.
[0043] Regarding the selection of positive electrode active material, An LMFP having an initial charge capacity of 165 mAh / g and an initial efficiency of 98% is selected, and a high-nickel ternary material having an initial charge capacity of 238 mAh / g and an initial efficiency of 86% (molar ratio of Ni:Co:Mn=0.83:0.12:0.05) is selected, and the LMFP and the high-nickel ternary material are mixed to form a positive electrode active material.
[0044] Regarding the selection of negative electrode active material, Silicon oxide and secondary carbon-coated graphite particles with an initial discharge capacity of 355 mAh / g and an initial efficiency of 95% are selected, and the secondary carbon-coated graphite particles and silicon oxide are mixed to form a negative electrode active material.
[0045] Regarding the selection of the lithium replenishment layer, Lithium powder is used to prepare the lithium replenishment layer.
[0046] Regarding the selection of separators, The separator used was a composite separator made of PP, ceramic, and adhesive, with the PP layer having a thickness of 7 μm, the ceramic layer having a thickness of 2 μm, and the adhesive layer having a thickness of 2 μm.
[0047] Regarding the selection of electrolyte, The electrolyte used in the lithium ion battery is one that contains lithium hexafluorophosphate as the main electrolyte.
[0048] The above selected positive electrode active material, negative electrode active material, lithium supplementary layer, separator, and electrolyte solution are used to manufacture the lithium ion battery in the following examples. The manufacturing flow includes the following steps S101 to S104.
[0049] In S101, NMP (N-methylpyrrolidone) and PVDF (polyvinylidene fluoride) are added to a stirrer and stirred for 1 hour, then conductive carbon black is added as a conductive agent and stirred for 0.5 hours, and then a positive electrode active material is added and stirred for 1.5 hours to form a positive electrode slurry, the positive electrode slurry is sieved and applied to a 12 μm thick aluminum foil current collector, the aluminum foil coated with the positive electrode slurry is vacuum dried at 80° C. for 12 hours, and finally, the dried aluminum foil coated with the positive electrode slurry is roll pressed and slit to obtain a positive electrode plate.
[0050] In S102, water, SBR and CMC are mixed and stirred in a stirrer for 1 hour, then conductive carbon black is added as a conductive agent and stirred for 0.5 hours, and then the negative active material is added and stirred for 1.5 hours to form a negative electrode slurry, the negative electrode slurry is sieved and applied to a 6μm copper foil current collector, the copper foil coated with the negative electrode slurry is vacuum dried at 100°C for 12 hours, and finally the dried copper foil coated with the negative electrode slurry is roll pressed and slit to obtain a negative electrode plate.
[0051] In S103, lithium powder is deposited on the surface of the negative active material of the negative plate to form a lithium-replenished negative plate.
[0052] In S104, the positive electrode plate, the separator, and the lithium-replenished negative electrode plate are placed in a battery case, the separator is positioned between the positive electrode plate and the lithium-replenished negative electrode plate, and then the battery case is sealed after injecting an electrolyte to obtain a lithium-ion battery.
[0053] Specifically, the lithium ion batteries in Examples 1 to 24 and Comparative Examples 1 to 7 are obtained. EXAMPLES
[0054] The mass fraction of the LMFP in the positive electrode active material is 80%, the mass fraction of the high nickel ternary material in the positive electrode active material is 20%, the mass fraction of the graphite in the negative electrode active layer is 86%, the mass fraction of silicon oxide δ is 14%, and the areal density of lithium in the lithium supplement layer is m2=a×M1×m1×δ×(1−η) / M2; In the formula, a is 1.1, x is 1.1, the discharge specific capacity M1 of the silicon oxide is 1435 mAh / g, the initial efficiency η of the silicon oxide is 85%, the specific capacity M2 of the lithium is 2400 mAh / g, and the surface density of the positive plate on both sides is 4.5 g / dm 2 The compaction density of the positive plate is 2.7 g / cm 3 The surface density m1 of the negative plate is 1.56 g / dm 2 The compaction density of the negative plate is 1.60 g / cm 3 The electrolyte filling coefficient is 2.9, and the surface density of lithium in the lithium replenishment layer is 0.0215 g / dm 2 It is. EXAMPLES
[0055] The mass fraction of the LMFP in the positive electrode active material is 78%, the mass fraction of the high nickel ternary material in the positive electrode active material is 22%, and the areal density of lithium in the lithium supplementary layer is 0.0215 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0056] The mass fraction of the LMFP in the positive electrode active material is 90%, the mass fraction of the high nickel ternary material in the positive electrode active material is 10%, and the areal density of lithium in the lithium supplementary layer is 0.0215 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0057] In the negative electrode active material of the negative electrode active layer, the mass fraction of graphite is 83%, the mass fraction of silicon oxide δ is 17%, and the surface density of lithium in the lithium supplementary layer is 0.0262 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0058] In the negative electrode active material of the negative electrode active layer, the mass fraction of graphite is 70%, the mass fraction of silicon oxide δ is 30%, and the surface density of lithium in the lithium supplementary layer is 0.0462 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0059] In the negative electrode active material of the negative electrode active layer, the mass fraction of graphite is 90%, the mass fraction of silicon oxide δ is 10%, and the surface density m1 of both sides of the negative electrode plate is 1.86 g / dm 2 The surface density of lithium in the lithium replenishment layer is 0.0184 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0060] a is 1.05, and the surface density of lithium in the lithium replenishment layer is 0.0206 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0061] a is 1.15, and the surface density of lithium in the lithium replenishment layer is 0.0225 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0062] x is 0.8, the discharge specific capacity M1 of the silicon oxide is 1470 mAh / g, the initial efficiency η of the silicon oxide is 83%, and the surface density of lithium in the lithium replenishment layer is 0.0250 g / dm2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0063] x is 0.6, the discharge specific capacity M1 of the silicon oxide is 1500 mAh / g, the initial efficiency η of the silicon oxide is 82%, and the surface density of lithium in the lithium replenishment layer is 0.0270 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0064] The surface density of the positive plate is 5g / dm 2 The surface density m1 of the negative plate is 1.92 g / dm 2 The surface density of lithium in the lithium replenishment layer is 0.0265 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0065] The compaction density of the positive plate is 2.8 g / cm 3 The surface density of lithium in the lithium replenishment layer is 0.0215 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0066] The surface density m1 of the negative plate is 1.8 g / dm 2 The surface density of lithium in the lithium replenishment layer is 0.0249 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0067] The compaction density of the negative plate is 1.65 g / cm 3 The surface density of lithium in the lithium replenishment layer is 0.0215 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0068] The electrolyte dosing factor is 3.2, and the remaining parameters are the same as in Example 1. EXAMPLES
[0069] The surface density of the positive plate is 4.2 g / dm 2 The surface density of lithium in the lithium replenishment layer is 0.0215 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0070] The surface density of the positive plate is 5.2g / dm 2 The surface density of lithium in the lithium replenishment layer is 0.0273 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0071] The compaction density of the positive plate is 2.5 g / cm 3 The surface density of lithium in the lithium replenishment layer is 0.0215 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0072] The compaction density of the positive plate is 2.9 g / cm 3 The surface density of lithium in the lithium replenishment layer is 0.0215 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0073] The surface density of the positive plate is 3.7 g / dm 2 The surface density m1 of the negative plate is 1.4 g / dm 2 The surface density of lithium in the lithium replenishment layer is 0.0193 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0074] The surface density m1 of the negative plate is 1.85 g / dm 2 The surface density of lithium in the obtained lithium replenishment layer was 0.0256 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0075] The compaction density of the negative plate is 1.45 g / cm 3 The surface density of lithium in the lithium replenishment layer is 0.0215 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0076] The compaction density of the negative plate is 1.80 g / cm 3 The surface density of lithium in the lithium replenishment layer is 0.0215 g / dm 2 and the remaining parameters are the same as in Example 1. EXAMPLES
[0077] The electrolyte dosing factor is 2.7, and the remaining parameters are the same as in Example 1. Comparative Example 1
[0078] The mass fraction of the LMFP in the positive electrode active material is 60%, the mass fraction of the high nickel ternary material in the positive electrode active material is 40%, and the areal density of lithium in the lithium supplementary layer is 0.0215 g / dm 2 and the remaining parameters are the same as in Example 1. Comparative Example 2
[0079] The mass fraction of the LMFP in the positive electrode active material is 98%, the mass fraction of the high nickel ternary material in the positive electrode active material is 2%, and the areal density of lithium in the lithium supplementary layer is 0.0215 g / dm 2 and the remaining parameters are the same as in Example 1. Comparative Example 3
[0080] In the negative electrode active material of the negative electrode active layer, the mass fraction of graphite is 60%, the mass fraction of silicon oxide δ is 40%, and the areal density of lithium in the obtained lithium supplementary layer is 0.0616 g / dm 2 and the remaining parameters are the same as in Example 1. Comparative Example 4
[0081] a is 1.2, and the surface density of lithium in the lithium replenishment layer is 0.0235 g / dm 2 and the remaining parameters are the same as in Example 1. Comparative Example 5
[0082] x is 0.45, the discharge specific capacity M1 of the silicon oxide is 2250 mAh / g, the initial efficiency η of the silicon oxide is 78%, and the surface density of lithium in the lithium replenishment layer is 0.0495 g / dm 2 and the remaining parameters are the same as in Example 1. Comparative Example 6
[0083] x is 1.7, the discharge specific capacity M1 of the silicon oxide is 1100 mAh / g, the initial efficiency η of the silicon oxide is 89%, and the surface density of lithium in the lithium replenishment layer is 0.0121 g / dm 2 and the remaining parameters are the same as in Example 1. Comparative Example 7
[0084] The negative plate has a two-sided areal density m1 of 2.46 g / dm2, excluding the lithium replenishment layer. 2 and the remaining parameters are the same as in Example 1.
[0085] For the lithium ion batteries in Examples 1 to 24 and Comparative Examples 1 to 7, the specific capacity of the positive electrode, the capacity retention rate after 2000 charge / discharge cycles, the thickness expansion rate of the negative electrode plate during a single charge / discharge cycle, the battery rate characteristics, and the DSC trigger temperature of the positive electrode active material were measured. The measurement process was specifically as follows.
[0086] Regarding the measurement of the specific capacity of the positive electrode, At room temperature (25°C), the lithium ion battery is charged at a rate of 0.1C and discharged at a rate of 0.1C. The charge / discharge voltage range is 2.5 to 4.2V. The charge / discharge cycle is performed three times, and the specific capacity of the positive electrode is calculated based on the coating amount of the electrode plate and the third discharge capacity of the lithium ion battery.
[0087] Regarding the measurement of capacity retention rate after 2000 charge / discharge cycles, The lithium ion battery is charged at a rate of 1C, discharged at a rate of 1C, and subjected to 2000 charge / discharge cycles at 45°C with a charge / discharge voltage range of 2.5V to 4.2V. The capacity retention rate of the battery after 2000 cycles is then obtained based on the ratio of the battery discharge capacity of the first cycle to that of the 2000th cycle.
[0088] Regarding the measurement of thickness expansion rate of negative plate during a single charge-discharge cycle, The positive and negative electrodes and the electrolyte are placed in the cavity where the electrode locator is located, and a vacuum evacuation process is performed before the measurement to remove any air bubbles in the cavity. It should be noted that when measuring the negative electrode, a positive electrode plate with small expansion, such as LMO (manganese), should be selected, and similarly, when measuring the positive electrode, LTO (lithium titanate) etc. is used. During the 0.1C charge and discharge process of the battery, the thickness change of the plate is collected to obtain the expansion rate of the plate.
[0089] Regarding the method for measuring the battery rate characteristics, At 25°C, charge at a constant current of 0.2C until the voltage reaches 4.2V, cut off at 0.05C at a constant voltage of 4.2V, leave for 10 minutes, and then discharge at a constant current of 0.2C until the voltage reaches 2.5V. This was repeated three times, and the third discharge capacity was recorded as C0. The cells were then fully charged at constant current and voltage of 0.2C0 and 5.0C0, respectively, and then fully discharged at the same current (1 / 3C). The discharge capacity at 0.2C0 was used as the standard, and the 5.0C0 discharge capacity and its ratio were used as indicators for evaluating the rate characteristics.
[0090] Regarding the measurement of the DSC trigger temperature of the positive electrode active material, The positive electrode active material of the lithium ion battery is charged to a fully charged state (specifically, charging at a constant current of 0.1 C until the cutoff voltage is 4.2 V, and then charging at a constant voltage of 4.2 V until the cutoff current is 0.05 C), and the fully charged positive electrode plate and electrolyte are placed in a high-temperature crucible and heated at a heating rate of 5° C. / min. The thermogram is measured with a differential scanning calorimeter (DSC) to observe the trigger temperature of thermal runaway of the positive electrode active material.
[0091] Table 1 shows the measurement data of the lithium ion batteries in Examples 1 to 24 and Comparative Examples 1 to 7.
[0092] [Table 1]
[0093] As can be seen from Table 1, the positive electrode specific capacity of the lithium ion batteries in Examples 1 to 24 is all greater than 150 mAh / g, the energy density of the lithium ion batteries is all greater than 250 Wh / kg, the lithium ion batteries in Examples 11 and 17 can reach 270 Wh / kg or more, the capacity retention rate of the lithium ion batteries after 2000 charge and discharge cycles is all greater than 76%, and in the case of the lithium ion battery in Example 8, it can reach 85%, the thickness expansion rate of the negative electrode after measurement of a single charge and discharge cycle of the lithium ion battery is all less than 13%, the thickness expansion rate of the negative electrode after measurement of a single charge and discharge cycle of the lithium ion batteries in Examples 7, 20 and 22 is only 8%, the ratio of the discharge capacity at 5.0 C to the discharge capacity at 0.2 C of the lithium ion battery is all higher than 81%, and the ratio of the discharge capacity at 5.0 C to the discharge capacity at 0.2 C of the lithium ion batteries in Examples 16 and 20 reaches 95%, showing high rate discharge characteristics. In terms of safety, by effectively blending LMFP and high-nickel ternary material, the DSC trigger temperature of the positive electrode active material of the lithium ion batteries in Examples 1 to 24 is higher than 255°C, that is, the batteries can operate safely within a range of 255°C or less, improving the safety of the lithium ion batteries.
[0094] None of the lithium ion batteries in Comparative Examples 1 to 7 can satisfy the multiple characteristic requirements of specific capacity, cycle retention rate, and safety. Specifically, compared to Example 1, the lithium ion battery in Comparative Example 1 has a large amount of ternary material added as a positive electrode active material, so that the capacity retention rate after 2000 charge / discharge cycles is 68%. Also, because the safety of the ternary material is low, the DSC trigger temperature of the positive electrode active material of the lithium ion battery in Comparative Example 1 is only 235° C., limiting the use of the lithium ion battery at high temperatures. Compared to Example 1, the lithium ion battery in Comparative Example 2 has a large amount of LMFP added as a positive electrode active material, so that the capacity retention rate after 2000 charge / discharge cycles is 68%. The positive electrode specific capacity is only 146.8mAh / g, and the energy density is only 235Wh / kg. Compared with Example 1, the lithium ion battery in Comparative Example 3 has a large amount of silicon oxide added as the negative electrode active layer, so the thickness expansion rate of the negative electrode of the lithium ion battery during a single charge and discharge process reaches 22%, which severely affects the cycle life of the lithium ion battery, and the capacity retention rate after 2000 charge and discharge cycles is 56%. Compared with Example 1, the lithium ion battery in Comparative Example 4 has a value of a that is too large, reaching 1.2. That is, the reserve amount of the lithium supplementary layer is too large, and the expansion during the charge and discharge process of the negative electrode is large, and the thickness expansion rate of the negative electrode during the initial charge and discharge process reaches 18%. In Comparative Example 5, the value of x is too small compared with Example 1, being only 0.45, and the discharge specific capacity M1 of the silicon oxide reaches 2250, but its initial efficiency η is 78%. The silicon oxide at this time is close to pure silicon, and the expansion during the single charge and discharge process of the negative electrode is large, which affects the cycle characteristics of the lithium ion battery, and the thickness expansion rate of the negative electrode during the single charge and discharge process is 24%. The capacity retention rate after 2000 charge-discharge cycles was only 50%. In Comparative Example 6, the value of x was too large, reaching 1.7, compared with Example 1, and the initial efficiency η of silicon oxide reached 89%, but the discharge specific capacity M1 was only 1100, which was unfavorable to improving the cycle characteristics of the lithium ion battery. The capacity retention rate after 2000 charge-discharge cycles was only 40%. Compared with Example 1, the lithium ion battery in Comparative Example 7 lacks a lithium supplementary layer, so the surface density on both sides of the negative electrode plate is too large, reaching 2.46 g / dm2 During the charging and discharging process, the negative active material consumes the active lithium of the positive active material, and the energy density of the lithium ion battery decreases, and the energy density is only 210Wh / kg.
[0095] Although the examples of the present application have been described above with reference to the drawings, the present application is not limited to the above specific embodiments, and the above specific embodiments are not limiting but merely illustrative. A person skilled in the art can implement many forms based on the suggestions of the present application without departing from the spirit of the present application and the scope of protection of the claims, and all of these fall within the scope of protection of the present application. [Explanation of symbols]
[0096] 1 Positive plate 11 Positive electrode active layer 12 Positive electrode current collector 2 negative plate 21 Negative electrode active layer 211 Composite layer 212 Lithium replenishment layer 22 Negative electrode current collector 3. Separator
Claims
1. A lithium ion battery including a positive electrode plate, a separator, and a negative electrode plate, the separator being provided between the positive electrode plate and the negative electrode plate, The positive electrode plate includes a positive electrode current collector and a positive electrode active layer, which are laminated in this order, and the positive electrode active material in the positive electrode active layer includes lithium manganese iron phosphate and a ternary material, and based on the total mass of the positive electrode active material, the mass percentage range of the lithium manganese iron phosphate is 70% to 90%, and the mass percentage range of the ternary material is 10% to 30%, The negative electrode plate includes a negative electrode current collector and a negative electrode active layer, which are laminated in order. The negative electrode active layer includes a composite layer and a lithium supplementary layer. The negative electrode active material in the composite layer is a carbon material and SiO x The mass percentage of the carbon material is in the range of 70% to 90% based on the total mass of the negative electrode active material, and the SiO x The mass percentage range of is 10% to 30%, and the areal density m of lithium in the lithium supplement layer 2 = a × M 1 ×m 1 ×δ×(1−η) / M 2 and In the formula, m 2 The unit is g / dm 2 And M 1 is SiO x The unit of the discharge specific capacity is mAh / g, and m 1 is the surface density of the negative plate on both sides, m 1 The unit is g / dm 2 and δ is the SiO x is the mass percentage of the material, and η is SiO x The initial efficiency of the button half cell is the ratio of the initial discharge capacity to the initial charge capacity, M 2 is the value of the specific capacity of lithium, the unit of the specific capacity is mAh / g, the value of a is in the range of 1.05 to 1.15, the value of x is in the range of 0.6 to 1.5, The general formula of the ternary material is LiNi a1 Co b1 X c1 O 2 , wherein 0≦a1≦1, 0≦b1≦1, 0≦c1≦1, and a1+b1+c1=1; X is at least one metal element of groups IIIB to VA; and the mass fraction of Ni in the ternary material is in the range of 80% to 95%.
2. Based on the total mass of the positive electrode active material, the mass percentage range of the lithium manganese iron phosphate is 78% to 83%, and the mass percentage range of the ternary material is 17% to 22%; Based on the total mass of the negative electrode active material, the mass percentage of the carbon material is in the range of 83% to 88%, and the SiO x The lithium ion battery according to claim 1, wherein the mass percentage range of is 12% to 17%.
3. The range of the surface density of the positive electrode plate on both sides is 4.5 g / dm 2 ~5.0g / dm 2 and the range of the compaction density of the positive electrode plate is 2.7 g / cm 3 ~2.8g / cm 3 3. The lithium ion battery according to claim 1 or 2,
4. The range of the surface density of the negative electrode plate is 1.56 g / dm 2 ~1.92g / dm 2 and the range of the compaction density of the negative electrode plate is 1.60 g / cm 3 ~1.65g / cm 3 The lithium ion battery according to any one of claims 1 to 3,
5. The lithium ion battery according to any one of claims 1 to 4, characterized in that the carbon material contains at least one of hard carbon and secondary carbon-coated graphite.
6. The lithium ion battery according to any one of claims 1 to 5, wherein the value of x is in the range of 0.8 to 1.
2.
7. The lithium ion battery according to any one of claims 1 to 6, characterized in that the electrolyte injection coefficient in the lithium ion battery is within a range of 2.9 to 3.
2.
8. The lithium ion battery according to any one of claims 1 to 7, characterized in that the separator includes a polymer layer, a ceramic layer, and an adhesive layer, which are laminated in this order, the polymer layer having a thickness ranging from 5.5 μm to 9 μm, the ceramic layer having a thickness ranging from 1.0 μm to 3.0 μm, and the adhesive layer having a thickness ranging from 1.0 μm to 3.0 μm.
9. The thickness range of the positive electrode current collector is 7 μm to 13.5 μm, and the thickness range of the negative electrode current collector is 3.5 μm to 7 μm. The lithium ion battery according to any one of claims 1 to 8.
Citation Information
Patent Citations
Mixed cathode materials
JP2014524133A
Lithium ion secondary battery
JP2016076317A
Positive electrode for lithium ion secondary battery and lithium ion secondary battery using the same
JP2018006129A
Nonaqueous electrolyte power storage device
JP2020177739A